Dynamic instability analysis of cavitating flow with liquid nitrogen in a converging–diverging nozzle. (25th June 2021) - Chen, Tairan; Mu, Zhendong; Huang, Biao; Zhang, Mindi; Wang, Guoyu
Highlights: A numerical framework for thermo-fluids is utilized to investigate liquid nitrogen. A modified one-dimensional model considering the thermodynamic effects is proposed. Dynamic instabilities of cavitating flow are numerically and theoretically analyzed. The modified one-dimensional model facilitates the development of engineering designs. Abstract: The purpose of this work is to investigate the dynamic instabilities of cavitating flow with liquid nitrogen in a converging–diverging (C–D) nozzle based on both the numerical and theoretical methods. Three temperatures Tthroat = 73.06 K, 77.63 K and 83.88 K representing three thermal cavitation modes respectively were studied. The simulations were set up according to the experiments. The results show that the numerical method could generally simulate the unsteady evolution of cavitating flows, and the corresponding pressure distribution for different cavitation mode. A modified one-dimensional model was proposed to investigate the dynamic instabilities and pressure fluctuations induced by the unsteady cavities. The modified one-dimensional model considering thermodynamic effects can accurately calculate the pressure fluctuation in the cavitation region. This indicates the mechanism of pressure and temperature fluctuations of cavitating flow with thermo-fluids. Further analysis indicates the pressure fluctuations in both non-cavitation and cavitation regions are not dominated by the cavity magnitude but the cavity volume acceleration. The modified one-dimensional model is crucial for designing and assessing the thermo-fluids apparatus or systems when cavitation occurs. The inertial mode and the transitional mode should be avoided to prevent the most significant pressure fluctuation and the maximum cavitation aggressiveness.